Botanical Composition, Grass Production, and Carrying Capacity of Pasture in Timor Tengah Selatan District - V. E. Se'u; P. D. M. H. Karti; L. Abdullah (Media Peternakan, 2015)
This study was conducted to analyze the botanical composition, grass production, carrying capacity, and potential production of nutrients in pasture located in Timor Tengah Selatan Regency. The experiment was conducted from February to July 2013, using field survey method. The botanical composition, grass production and carrying capacity on real condition were analyzed descriptively, while the grass production and carrying capacity based of cutting arrangement were analyzed by using randomized block factorial design with 3 altitude locations (Sub District of Mollo Utara with altitude of 1007 m above sea level; Sub District of Noebeba, 500 m ASL, and Sub District of Amanuban Selatan, 65 m ASL) x 2 cutting intervals (1 and 2 month) and 5 replications. The results showed that the grass type dominated the pasture in the Sub District of Mollo Utara, while legum type was more dominant in the pasture in the Sub Districts of Noebeba and Amanuban Selatan. The potential production of dry matter grass in Timor Tengah Selatan Regency based on real condition was 150 to 390 kg/ha/yr, this could accommodate 0.24 to 0.63 AU/ha/yr. The arrangement of cutting interval by 1 month in Mollo Utara and 2 months in Noebeba and Amanuban Selatan could increase (P<0.05) grass production and carrying capacity. The potential productions of grass nutrients were higher in Sub District of Mollo Utara, while potential production of grass dry matter was higher in Sub Districts of Noebeba and Amanuban Selatan. It was concluded that grass dry matter potential production and carrying capacity in Timor Tengah Selatan Regency were low. The arrangement of cutting interval could increase grass dry matter potential production, carrying capacity, nutrition production, and quality of nutrition.Key words: carrying capacity, grass, pasture, Timor Tengah Selatan